Efektivitas Pengelolaan Dana Bantuan Operasional Sekolah dalam Meningkatkan Mutu Pendidikan : (Studi Kasus di SD Negeri Danau Ina Oesapa) - Frida Orpa Bolla; Melkisedek N.B.C. Neolaka; Ardy Yosafat Pandie; Hendrik Toda (Dharma Ekonomi, 2024)
This research is entitled The Effectiveness of School Operational Assistance Fund Management in Improving the Quality of Education (Case Study at SD Negeri Danau Ina Oesapa). The purpose of this study is to analyze the management of school operational assistance funds at Lake Ina Oesapa State Elementary School in improving the quality of education, which includes the planning, implementation, and evaluation stages. This study uses a descriptive qualitative approach, while the type of research used in this study is a descriptive case study research. The results of the study show that SD Negeri Danau Ina Oesapa in the effectiveness of the management of school operational assistance funds (BOS) in improving the quality of education can be said to be effective. This can be seen from the first, the planning for the management of BOS funds at SD Negeri Ina Oesapa begins by compiling RKAS based on needs and in accordance with the components of BOS fund financing to improve the quality of education. Second, the implementation of BOS fund management at SD Negeri Ina Oesapa is adjusted to the RKAS which has been determined to improve the quality of education and in accordance with the BOS fund guidelines. Third, the evaluation of the management of BOS funds at SD Negeri Ina Oesapa is carried out by the principal and the government (Kupang City Education and Culture Office), the evaluation is carried out at the end of each year to correct errors in the management of BOS funds. Even so, there are still inhibiting factors in the management of school operational assistance (BOS) funds, namely, the disbursement of funds often experiences delays in BOS funds, schools are limited in making heavy repairs so that schools are still experiencing a shortage of rooms, and some students whose names are not readable in financial data. It is recommended that the central government needs to accelerate the distribution of BOS funds so that it is on time. Schools are expected to continue to develop facilities and infrastructure.